2020
DOI: 10.2196/15725
|View full text |Cite
|
Sign up to set email alerts
|

The Kids Obesity Prevention Program: Cluster Randomized Controlled Trial to Evaluate a Serious Game for the Prevention and Treatment of Childhood Obesity

Abstract: Background Health games provide opportunities for the treatment and prevention of childhood obesity. We developed a motion-controlled serious game for children that addresses 3 core topics of nutrition, physical activity, and stress coping. It is the first serious game that extensively targets the dietary energy density principle (DED-P) in relation to nutrition. The game is intended to provide an additional educational component for the prevention and treatment of obesity in children. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 74 publications
3
41
0
2
Order By: Relevance
“…All included studies were clinical trials [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The total sample was 11,280 children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were clinical trials [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The total sample was 11,280 children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…To date, four research groups took the initiative to develop multidisciplinary serious games including different game modules that can be used to promote healthy behaviors in children with obesity. Three of them were recently published ( Espinosa-Curiel et al, 2020 ; Mack et al, 2020 ; Ruggiero et al, 2020 ), while one is still in progress ( Mâsse et al, 2020 ). The overall content (i.e., available online) and outcome goals were to provide knowledge, enhance motivation, and encourage behavior change related to healthy eating, PA, and stress coping.…”
Section: Multidisciplinary Serious Gamementioning
confidence: 99%
“…A subsequent study by Mack et al (2020) assessing the effects of their multidisciplinary game among children aged 8–12 years, indicated that players increased knowledge in the areas of nutrition and stress coping, and were able to apply the dietary energy density principle of nutrition education. The stress coping is an important factor in weight regulation, as stress can be associated with poor dietary habits and low physical activity, especially when an individual faces challenges that surpass his or her coping skills ( Mack et al, 2020 ). No changes at the behavioral level (e.g., media consumption and PA level) occurred because of the study focus (i.e., nutrition education) and design.…”
Section: Multidisciplinary Serious Gamementioning
confidence: 99%
See 1 more Smart Citation
“…The principles of weight management aim to reduce energy intake by improving diet and eating habits, i.e., modifications in the macronutrient distribution of energy intake, and to enhance energy expenditure by increasing physical activity and avoiding a sedentary lifestyle [ 4 ]. From a nutritional point of view, portion size and energy density [ 5 , 6 ] of foods as well as eating frequency [ 7 ] are key factors of weight management [ 8 ]. In view of the increase in portion sizes over recent decades, it is important to be familiar with appropriate food portion sizes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%